2019
DOI: 10.1007/s11116-019-10072-0
|View full text |Cite
|
Sign up to set email alerts
|

Using multiple hybrid spatial design network analysis to predict longitudinal effect of a major city centre redevelopment on pedestrian flows

Abstract: Predicting how changes to the urban environment will affect town centre vitality, mediated as pedestrian flows, is important for environmental, social and economic sustainability. This study is a longitudinal investigation of before and after urban environmental change in a town centre and its association with vitality. The case study baseline is Cardiff town centre in 2007, prior and after major changes instigated by re-configuring Cardiff public and quasi-public street layout due to implementation of the St … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Street-network centrality should be accounted for before locating growth and consolidation plans. Specialised software for measuring network-based relationships in cities supplement generic GIS network platforms and include Space Syntax (Hillier, 1999), Urban Network Analysis (UNA) (Sevtsuk and Mekonnen, 2012) and sDNA (Cooper et al, 2019). Methodological developments from wider network science have found their way into urban studies, such as the early application of network-based centrality measures to urban design (Hillier and Hanson, 1984), network kernel density estimation (Han et al, 2019) and network evolution models (Masucci et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Street-network centrality should be accounted for before locating growth and consolidation plans. Specialised software for measuring network-based relationships in cities supplement generic GIS network platforms and include Space Syntax (Hillier, 1999), Urban Network Analysis (UNA) (Sevtsuk and Mekonnen, 2012) and sDNA (Cooper et al, 2019). Methodological developments from wider network science have found their way into urban studies, such as the early application of network-based centrality measures to urban design (Hillier and Hanson, 1984), network kernel density estimation (Han et al, 2019) and network evolution models (Masucci et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We constructed a set of parsimonious models that regress street network link-based cluster descriptors on link-based centrality using sDNA+, a plug-in for ArcGIS (Chiaradia et al, 2019; Cooper et al, 2019), with controls for housing density, other choice dimensions and land price. Measuring the clustering tendencies of different kinds of economic units in urban space has been a major challenge in assessing agglomeration patterns, scale and intensity of facilities, and there is a need to diversify the methodology to accurately measure spatial concentration or dispersion of economic units in an area (Garracho-Rangel et al, 2013; Law, 2017; Scoppa and Peponis, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We used the average betweenness in a park’s catchment to indicate the quality of street connectivity of neighbourhoods around a park. Betweenness centrality was measured using sDNA (Cooper et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Cooper et al noted that for Angular-Euclidean hybrid metric, 0.25 ≤ a ≤ 0.5 gave good results [84]. It has been reported that a calibration of half angular–half Euclidean metric gives a stable result in terms of interpreting pedestrian movement [85].…”
Section: Methodsmentioning
confidence: 99%